Single Synapse LTP: A Matter of Context? - Kruijssen, Dennis L. H.; Wierenga, Corette J. (Frontiers in Cellular Neuroscience, 2019)
The most commonly studied form of synaptic plasticity is long-term potentiation (LTP). Since 15 years, it is possible to induce structural and functional LTP in dendritic spines using two-photon glutamate uncaging, allowing for studying the signaling mechanisms of LTP with single synapse resolution. In this review, we compare different stimulation methods to induce single synapse LTP and discuss how LTP is expressed. We summarize the underlying signaling mechanisms that have been studied with high spatiotemporal resolution. Finally, we discuss how LTP in a single synapse can be affected by excitatory and inhibitory synapses nearby. We argue that single synapse LTP is highly dependent on context: the choice of induction method, the history of the dendritic spine and the dendritic vicinity crucially affect signaling pathways and expression of single synapse LTP.